2022
DOI: 10.1038/s42003-022-03667-4
|View full text |Cite
|
Sign up to set email alerts
|

Repeated ketamine anesthesia during neurodevelopment upregulates hippocampal activity and enhances drug reward in male mice

Abstract: Early exposures to anesthetics can cause long-lasting changes in excitatory/inhibitory synaptic transmission (E/I imbalance), an important mechanism for neurodevelopmental disorders. Since E/I imbalance is also involved with addiction, we further investigated possible changes in addiction-related behaviors after multiple ketamine anesthesia in late postnatal mice. Postnatal day (PND) 16 mice received multiple ketamine anesthesia (35 mg kg−1, 5 days), and behavioral changes were evaluated at PND28 and PND56. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Similarly to our study, tolerance to repeated treatment with ketamine was found regarding its anesthetic efficacy [40][41][42][43] and psychotomimetic effects [44]. The tolerance reported in our study may indicate that repeated treatment of patients suffering from depression with ketamine or ketamine enantiomers would progressively result in fewer side effects.…”
Section: Plos Onesupporting
confidence: 87%
“…Similarly to our study, tolerance to repeated treatment with ketamine was found regarding its anesthetic efficacy [40][41][42][43] and psychotomimetic effects [44]. The tolerance reported in our study may indicate that repeated treatment of patients suffering from depression with ketamine or ketamine enantiomers would progressively result in fewer side effects.…”
Section: Plos Onesupporting
confidence: 87%
“…The thickness of dendrites influences the transmission of postsynaptic potentials by affecting electrical resistance, with thicker dendrites propagating signals more quickly than thin dendrites (Loopuijt et al , 2007;Li et al , 2019). It is reported that increased dendritic diameter in COX-2 knockin mice may result in excitatory signaling imbalances in the cerebellum (Leeet al , 2017;Sohal & Rubenstein, 2019;Cui et al , 2022). In our study, we demonstrate a significant decrease in dendritic spine density in COX-2KO mice compared to WT ones, suggesting the critical role of COX-2 on synaptic plasticity in the hippocampus CA1.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine has a strong addiction potential via inducing SA and CPP [ 85 , 86 , 87 ]. However, there is no systematic review of the specific mechanisms of ketamine addiction.…”
Section: Molecular Mechanism Of Non-opioid Anesthetic Drug Addictionmentioning
confidence: 99%